William Faulkner : seeing through the South - Matthews, John T. (Blackwell introductions to literature ;, 2009)
This succinct, yet comprehensive account of William Faulkner's literary career, novels, and key short stories offers an imaginative topography of his efforts to reckon with his Southern past, to acknowledge its modernization, and to develop his own modernist method.:.; Provides a brief but comprehensive account of Faulkner's literary career, through discussion of his novels and key short stories.; Offers an imaginative topography of Faulkner's efforts to reckon with his Southern past, to acknowledge its modernization, and to develop his own modernist method.; Draws on various specialized criti.